Route of administration of contraceptives containing desogestrel/etonorgestrel and insulin sensitivity: a prospective randomized study - Cagnacci, Angelo; Ferrari, Serena; Tirelli, Alessandra; Zanin, Renata; Volpe, Annibale (Contraception (Stoneham), 2009)
The study was conducted to investigate whether hormonal contraceptives administered via the oral and vaginal route exert a similar effect on insulin sensitivity (SI). This is a prospective, randomized study performed in the University Hospital. Subjects were healthy lean young women, needing a hormonal contraceptive, randomly allocated to receive for 6 months (a) an oral contraceptive (OC) containing 30 mcg ethinylestradiol (EE)/150 mcg desogestrel (DSG) (high-estrogen group; n=12), (b) an OC containing 20 mcg EE/150 mcg DSG (low-estrogen group; n=12) and (c) a vaginal ring contraceptive releasing, per day, 15 mcg EE/120 mcg etonorgestrel, the active DSG metabolite ( n=12). SI and glucose utilization independent of insulin (Sg) were evaluated by the minimal model method. Modifications of total, high-density lipoprotein (HDL) and low-density lipoprotein cholesterol and triglycerides were also evaluated. Sg did not vary with any treatment. SI decreased during OCs (5.74±0.49 vs. 3.86±0.44; p=.0005), independently of the high/low-estrogen dose. SI did not decrease during vaginal ring use (4.64±1.03 vs. 5.25±1.36; p=.57; p=.019 vs. oral). Total cholesterol and HDL cholesterol increased (p=.02) during OCs, independently of the dose. Triglycerides increased during both oral (p=.01) and vaginal (p=.032) contraceptive use. The present data indicate that in contrast to OC use, vaginal contraception with the ring does not deteriorate SI. The vaginal ring may represent an appropriate choice for long-term contraception in women at risk for developing diabetes mellitus or metabolic syndrome.